1982
DOI: 10.1063/1.444268
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of polar negative ions

Abstract: Potential energy curves of ground and excited states of tetra halomethanes and the negative ionsThe spectra of electronically excited states of strongly polar negative ions are discussed in terms of general features that may be predicted for such systems. The general properties are then studied through a systematic treatment of lithium halide and lithium hydride anions. Only one or two excited electronic levels exist for these systems, and the binding energies are so low that a limited number of bound rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 25 publications
3
79
1
Order By: Relevance
“…The role of non-BO coupling has been studied by Garrett, who concluded that such couplings are negligible for dipole-bound states with electron binding energies (E bind 's) much larger than the molecular rotational constants. 53 The simplest theoretical approach to estimate E bind is based on Koopmans' theorem. 54 The KT binding energy (E bind KT ) is the negative of the energy of the relevant unfilled orbital obtained from a Hartree-Fock self-consistent field (SCF) calculation on the neutral molecule.…”
Section: Hydrazine and Its Tautomermentioning
confidence: 99%
“…The role of non-BO coupling has been studied by Garrett, who concluded that such couplings are negligible for dipole-bound states with electron binding energies (E bind 's) much larger than the molecular rotational constants. 53 The simplest theoretical approach to estimate E bind is based on Koopmans' theorem. 54 The KT binding energy (E bind KT ) is the negative of the energy of the relevant unfilled orbital obtained from a Hartree-Fock self-consistent field (SCF) calculation on the neutral molecule.…”
Section: Hydrazine and Its Tautomermentioning
confidence: 99%
“…They found that if a negative meson is captured by a hydrogen nucleus, the binding energy of the electron becomes zero for the electric dipole moment of a meson-proton system µ cr = 1.625 D. Later this result was generalized to the case of an extended dipole with an infinite moment of inertia [40]. Lifting the adiabatic approximation by considering the rotational degrees of freedom of the anion [17][18][19][20][21][22] turned out to be crucial; it also boosted the critical value of µ to about 2.5 D. For anions with µ > µ cr , the number of bound states of the electron becomes finite, and the critical electric dipole moment µ cr depends on the moment of inertia of the molecule. In the non-adiabatic calculations, the pseudo-potential was used to take into account finite size effects, repulsive core, polarization effects, and quadrupolar interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Our conclusions are based on a series of electronic structure calculations, as well as fixed-nuclei electron -HOCO scattering calculations. The dipole moment of the trans-radical computed at the MP2 level of theory is 2.84 Debye, which is larger than the threshold value that Garret [40] suggests is needed to bind an electron. Furthermore, our CISD calculation using diffuse sets of basis functions, predicts the binding energy of the dipole-bound anion to be 0.48 meV.…”
Section: Discussionmentioning
confidence: 89%
“…The change is demonstrated by the angular distributions plotted in Fig 5b. Although the angular distributions near threshold are consistent with experiment, the calculations do not Fermi and Teller [39] were the first to show that a nonrotating dipole with magnitude d>1.625 D can support an electron in an infinite number of bound states. A number of subsequent studies demonstrated that, even in the low temperature limit, rotational motion becomes important and the critical dipole-moment and the number of bound states depend on the moment of inertia of the molecule [40,41]. For small molecules, Garret [40] has provided the rough rule of thumb that a dipole moment must be greater than 2.0D to bind an electron by one meV or more.…”
Section: A Photodetachment Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation